Positive geographic correlation between soldiers’ weapon size and defensive prowess in a eusocial aphid, Ceratovacuna japonica - Mitsuru Hattori; Masato Ono; Takao Itino (Scientific Reports, 2022)
Abstract Some aphid species produce a soldier caste with enlarged forelegs and horns (weapons). It has been hypothesised that the evolution of morphological specialization by soldiers in social aphids is accelerated by high predation pressure, but this possibility has not been tested. Here, we investigated the relationship between local predator abundance and soldiers’ weapon size and aggressiveness in a prey–predator system comprising a eusocial aphid, Ceratovacuna japonica, and its predators (larvae of the butterfly Taraka hamada and of the moth Atkinsonia ignipicta) in two populations with different predator abundances. We found that the soldiers in the predator-abundant population had larger weapons and were more aggressive than those in the population with lower predator abundance. Furthermore, the soldiers’ defensive prowess (evaluated as the survival of aphids in the presence of predators) was greater in the predator-abundant population. These results provide the first evidence that a population of eusocial aphids experiencing high predation pressure has soldiers with pronounced defensive traits and defensive prowess.